Determinants of Health Intervention Success: The Role of Transformational and Servant Leadership in Community Settings - Siti Umrana; Herman Herman; Risnawati Risnawati (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2026)
The effectiveness of health interventions is determined by multiple factors, such as leadership, participation, and environmental support. This study analyzes the determinants and most influential factors contributing to the success of health interventions. A quantitative approach with a cross-sectional analytical design was employed, involving 194 respondents selected through proportional random sampling in Lepo-Lepo (Southeast Sulawesi Province). Data analysis utilized the chi-square test and logistic regression. The findings indicate that leadership capacity (p=0.021; OR=2.130), participation (p=0.000; OR=3.640), communication skills (p=0.000; OR=8.016), support in decision making (p=0.000; OR=4.800), access to health facilities (p=0.000; OR=4.759), local culture and norms (p=0.012; OR=2.231), transformational leadership style (p=0.000; OR=15.171), and servant leadership style (p=0.011; OR=2.231) significantly affect the success of health interventions. In contrast, community credibility and trust (p=0.869) and regional policies (p=0.843) do not demonstrate a significant effect. The most dominant factor was transformational leadership style, with an OR of 12.409, meaning leaders with a transformational style were more than 12 times more likely to achieve intervention success than leaders who did not. These results confirm that leadership quality and participatory support, particularly transformational leadership style and effective communication skills, are critical to the success of health interventions. One of the implications of the results of this study for public health is that they emphasize that effective interventions require leaders capable of inspiring and facilitating transformational change, not just managing technical matters, and communication is a core skill that must be developed at every level of health management, particularly given its role in strengthening community compliance and trust. Keywords: Health Interventions, Leadership, Participation, Communication, Transformational Leadership.